Lottery attractiveness and presentation mode of probability and value information - Fiedler, Klaus; Unkelbach, Christian (Journal of behavioral decision making, 2011)
The attractiveness of lotteries that vary in p (probability) and o (outcome) depends on the presentation mode of p and o information. Extending previous findings on temporally experienced p, we manipulate the numerically stated versus spatially experienced format of both p (graphical presentation of a distribution of lottery tickets in an urn) and o (distribution of money notes). Lottery attractiveness ratings were sensitive to the expected value (EV), but p received more weight than o at constant EV levels (p-dominance). Both EV sensitivity and p-dominance were enhanced for experienced p and numerical o. This format particularly revealed the unattractiveness of low-p lotteries. Experiencing p was functional in terms of accuracy and high-risk avoidance, but only when the task environments rendered p diagnostic of EV. The presentation mode manipulations did not affect the initial perception stage but the relative weighting of p and o in the final judgment integration stage. Copyright © 2010 John Wiley & Sons, Ltd.
First published: 24 December 2010
Gesehen am 09.05.2022